PERANAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DALAM TINJAUAN HUBUNGAN NON-LINEAR Kasus Perusahaan yang Terdaftar di Bursa Efek Indonesia - Elok Pakaryaningsih (Benefit: Jurnal Manajemen dan Bisnis, 2008)
This research examines the effect of institutional ownership on firm value. In doingso, institutional ownership will be divided into two groups; passive owner and active owner.The active owner who holds more than 5 percent of stock is hypothesized to have positiverelationship with firm value. However, this positive relationship will decline considerably asthe percentage of ownership increases. The other variables, namely; passive institutionalownership, public ownership, and firm size will be used as well to examine the consistentrelationship between institutional ownership and firm value. Rather than examining itlinearly, this research intends to examine the non-linear effect of institutional ownership onfirm value. The samples are drawn from all firms listed at the Jakarta Stock Exchange from2002 to 2005. Using the non-linear regression analysis, the results show the existence of nonlinearrelationship between active institutional owner andfirm value in Indonesia.